2014
DOI: 10.1186/1465-9921-15-57
|View full text |Cite
|
Sign up to set email alerts
|

Clonally expanded human airway smooth muscle cells exhibit morphological and functional heterogeneity

Abstract: BackgroundMesenchyme-derived airway cell populations including airway smooth muscle (ASM) cells, fibroblasts and myofibroblasts play key roles in the pathogenesis of airway inflammation and remodeling. Phenotypic and functional characterisation of these cell populations are confounded by their heterogeneity in vitro. It is unclear which mechanisms underlie the creation of these different sub-populations.The study objectives were to investigate whether ASM cells are capable of clonal expansion and if so (i) wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The doubling time for human ASM cells isolated from healthy non-asthmatic donor lungs varies from 36 to 52 h as reported in previous studies (7,12,15). Rate of proliferation of ASM cells within a culture shows high degree of variability (17). Further, it has been shown that primary human ASM cells exhibit heterogeneity that dictates many functional outcomes (to both endogenous and exogenous stimuli) such as cell proliferation, growth, calcium-, chemokine-, cytokine-, extracellular matrix (ECM)release (4,6,15).…”
mentioning
confidence: 59%
“…The doubling time for human ASM cells isolated from healthy non-asthmatic donor lungs varies from 36 to 52 h as reported in previous studies (7,12,15). Rate of proliferation of ASM cells within a culture shows high degree of variability (17). Further, it has been shown that primary human ASM cells exhibit heterogeneity that dictates many functional outcomes (to both endogenous and exogenous stimuli) such as cell proliferation, growth, calcium-, chemokine-, cytokine-, extracellular matrix (ECM)release (4,6,15).…”
mentioning
confidence: 59%
“…Although ASMCs exhibits heterogeneous properties (Ma, Li, & Stephens, ; Singh, Billington, Sayers, & Hall, ), it is likely that changes in the phenotype of ASMC occur in the disease progression of asthma. This view is supported by in vivo observation that the degree of airway responsiveness is variable depending on the severity of asthma symptoms (Busse, ).…”
Section: Discussionmentioning
confidence: 99%